Effects of Hubbard U correction on the structural and electronic properties of rutile, anatase and brookite TiO2. (2022) - Johari, N.A.; Hamzah, N.; Faizal, A.F.A.; Samat, M.H.; Hassan, O.H.; Ali, A.M.M.; Yahya, M.Z.A.; Taib, M.F.M.
Abstract: In this work, the first-principles calculations using density functional theory (DFT) was applied to calculate the structural and electronic properties of anatase, rutile and brookite TiO2 phases. The effects of Hubbard U correction on the structural and electronic properties of rutile, anatase TiO2 were explored using the local density approximation (LDA) and generalized gradient approximation (GGA) for Perdew-Burke-Ernzerhof (PBE) and Perdew-Burke-Ernzerhof for solids (PBEsol) method by applying Hubbard corrections Ud in Ti 3 d states and Up in O 2 p states. There are changes in the structural parameters caused by the Hubbard U correction in Ti d states and O p states. The best agreement of U values to improve the electronic band gap of rutile was found at Ud  = 3.0 eV and Up  = 7.0 eV from LDA, Ud  = 2.0 eV, Up  = 6.0 eV from GGA-PBEsol for anatase and Ud  = 3.0 eV and Up  = 4.0 eV for brookite using GGA-PBEsol. The combination of both Ud and Up correction terms managed to widen the band gap of rutile, anatase and brookite TiO2 which is close to the experimental value.